Efektywność wykorzystania prywatnych sieci wirtualnych (VPN) w przedsiębiorstwie - Chojnacka, Anna (Effectiveness of virtual private network (VPN) application in the enterprise, 2006)
The possibilities of VPN (Virtual Private Network) application in the enterprise are presented in the article. The author analyses both benefits and costs of such solution in comparison to other available technologies used for data transfer. The article also concerns the necessity of choosing the appropriate technologies supporting the general strategy of the enterprise.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1134, s. 92-99